2016
DOI: 10.1186/s12864-016-2680-8
|View full text |Cite
|
Sign up to set email alerts
|

Xylan degradation by the human gut Bacteroides xylanisolvens XB1AT involves two distinct gene clusters that are linked at the transcriptional level

Abstract: BackgroundPlant cell wall (PCW) polysaccharides and especially xylans constitute an important part of human diet. Xylans are not degraded by human digestive enzymes in the upper digestive tract and therefore reach the colon where they are subjected to extensive degradation by some members of the symbiotic microbiota. Xylanolytic bacteria are the first degraders of these complex polysaccharides and they release breakdown products that can have beneficial effects on human health. In order to understand better ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 43 publications
5
59
0
Order By: Relevance
“…This PUL comprised a GH3 (e.g., xylosidase), a GH10 (e.g., β-xylanase) and two sulfatase genes, together with an adjacent putative PUL containing a GH128 (β-glucanase) and four sulfatases genes. A similar PUL with GH3 and GH10 was shown to be upregulated with xylan in the human gut bacterium Bacteroides xylanisolvens [62]. Xylans are also components of marine phytoplankton [63], and high xylanase activities have been reported for many ocean provinces [64].…”
Section: Pul Repertoiresmentioning
confidence: 81%
“…This PUL comprised a GH3 (e.g., xylosidase), a GH10 (e.g., β-xylanase) and two sulfatase genes, together with an adjacent putative PUL containing a GH128 (β-glucanase) and four sulfatases genes. A similar PUL with GH3 and GH10 was shown to be upregulated with xylan in the human gut bacterium Bacteroides xylanisolvens [62]. Xylans are also components of marine phytoplankton [63], and high xylanase activities have been reported for many ocean provinces [64].…”
Section: Pul Repertoiresmentioning
confidence: 81%
“…100 PULs; however, strikingly few homologous PULs are shared between them, suggesting that these two symbionts have distinct glycan niches (39). Similarly, recent transcrip-tomic analyses indicated that B. xylanisolvens dynamically responds to discrete structures of pectins and xylans through several differentially regulated PULs (91,92). Such studies reflect the exquisite nutrient adaptation of individual Bacteroidetes bacteria.…”
Section: Pulomicsmentioning
confidence: 87%
“…Attempts to define PUL boundaries in the absence of expression data were also reported in the genome publication of Capnocytophaga canimorsus Cc5 ( 10 ). Moreover, several specific analyses have focused on the degradation of defined polysaccharides by their corresponding PULs, including plant (fructan ( 11 ), pectin ( 12 ), xylan ( 13 , 14 ), xyloglucan ( 15 ) and type II rhamnogalacturonan (RGII) ( 16 )) and non-plant (α-mannan ( 17 ), galactomannan ( 18 ), 1,6-β-glucan ( 19 ), mucin ( 20 ), sialoglycoconjugates ( 21 ), N-glycan ( 17 , 22 24 ), heparin and heparan sulfate ( 25 ), chitin ( 26 ), alginate and laminarin ( 27 )) polysaccharides. To facilitate the retrieval of characterized PULs by their cognate substrate, a new field appears in the PULDB homepage, to search for a given character substring within the PUL substrate labels.…”
Section: Literature-derived Puls Cognate Substrates and New Cazymesmentioning
confidence: 99%